2023
DOI: 10.3390/nu15010236
|View full text |Cite
|
Sign up to set email alerts
|

Ionized Magnesium: Interpretation and Interest in Atrial Fibrillation

Abstract: Background: Magnesium (Mg) is often used to manage de novo atrial fibrillation (AF) in the emergency department (ED) and intensive care unit (ICU). Point of care measurement of ionized magnesium (iMg) allows a rapid identification of patients with impaired magnesium status, however, unlike ionized calcium, the interpretation of iMg is not entirely understood. Thus, we evaluated iMg reference values, correlation between iMg and plasmatic magnesium (pMg), and the impact of pH and albumin variations on iMg levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
1
12
1
Order By: Relevance
“…These ndings support to the utilization of point-of-care analyzers for assessing iMg status in hospitalized patients, particularly when timely clinical decisions are necessary to guide patient management, including cases involving cardiac arrhythmia. (20) In the present study, signi cant discrepancies were observed in the prevalence of dysmagnesemia when comparing the use of iMg and tMg concentrations. Which is in concordance with previous studies.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…These ndings support to the utilization of point-of-care analyzers for assessing iMg status in hospitalized patients, particularly when timely clinical decisions are necessary to guide patient management, including cases involving cardiac arrhythmia. (20) In the present study, signi cant discrepancies were observed in the prevalence of dysmagnesemia when comparing the use of iMg and tMg concentrations. Which is in concordance with previous studies.…”
Section: Discussionmentioning
confidence: 50%
“…(13) One study found that the prevalence of hypomagnesemia de ned as iMg concentrations less than 0.48 mmol/L, was 12.7% in patients presenting to the emergency department with de novo AF. (20) Another study including 31 patients following abdominal surgery, found that both tMg and iMg concentrations decreased during surgery, with a strong correlation between both. (13) Overall, hypermagnesemia is increasingly recognized as an issue among hospitalized patients.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, blood samples collected in lithium heparinized syringes from 125 healthy adults from the United Kingdom and stored in Sarstedt Monovette ® serum gel blood collection tubes, resulted in iMg reference range of 0.45–0.60 mmol/L [ 18 ]. Furthermore, a French study, using the direct ISE technique for 80 patients who visited the emergency department, established a reference range of 0.48 to 0.65 mmol/L [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results were inconsistent, most likely due to pathophysiological interference and variation in the analytical methodologies [ 23 ]. Furthermore, the stability of analytes obtained for determining iMg concentration has not been established [ 24 ]. Such discrepancies in measurement methods and questionable stability, iMg concentration, and its use as a guide in treatment are not common in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, a number of studies were performed to investigate the association between Ca/P/Mg levels and various diseases. Mg was closely with the risk of cardiovascular diseases ( 40 ). Decreased level of Mg was linked to the impaired glucose homeostasis, insulin function and inflammation ( 41 ).…”
Section: Discussionmentioning
confidence: 99%